Pengaruh Social Media Marketing Terhadap Minat Berkunjung Ke Destinasi Wisata Pemandian Air Soda Tarutung - Daniel Adi Putra Pangaribuan; Christian B. Alexander L. Tobing (CV. Kurnia Grup, 2026)
This study aims to determine whether social media marketing influences the intention to visit the tourist destination Tarutung Soda Water Baths. A quantitative research method was employed, utilizing hypothesis testing—specifically the partial test (t-test) and the coefficient of determination (R²)—with data processed using SPSS Version 25. The sample size was 100 respondents, determined using the Slovin formula. The study concludes that the social media marketing variable (X) has a positive and significant partial effect on the intention to visit (Y), as evidenced by a calculated t-value exceeding the t-table value (9.561 > 1.9844). Furthermore, the regression result of 0.695 indicates that social media marketing (X) positively and significantly influences the intention to visit (Y) and represents a strong contributing factor. Consequently, the R-squared value was found to be 48.3%, while the remaining 51.7% is attributed to other variables.